2020
DOI: 10.1038/s42003-020-01246-z
|View full text |Cite
|
Sign up to set email alerts
|

Omental macrophages secrete chemokine ligands that promote ovarian cancer colonization of the omentum via CCR1

Abstract: The omentum is the most common site of ovarian cancer metastasis. Immune cell clusters called milky spots are found throughout the omentum. It is however unknown if these immune cells contribute to ovarian cancer metastasis. Here we report that omental macrophages promote the migration and colonization of ovarian cancer cells to the omentum through the secretion of chemokine ligands that interact with chemokine receptor 1 (CCR1). We found that depletion of macrophages reduces ovarian cancer colonization of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(48 citation statements)
references
References 58 publications
2
37
0
4
Order By: Relevance
“…While the omentum, a highly vascularized organ critical in the development of PCa is a large organ in humans, it does not play the same role in mice [53] (Figure 2). Despite this fact, the omentum of mice is considered an interesting organ for immune studies of peritoneal carcinomatosis, especially to understand the role of resident macrophages that promote peritoneal carcinomatosis [54][55][56]. However, on the whole, syngeneic PCa models are not entirely a bona fide model for PCa in patients.…”
Section: Pca Mouse Models 21 Pca Syngeneic Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the omentum, a highly vascularized organ critical in the development of PCa is a large organ in humans, it does not play the same role in mice [53] (Figure 2). Despite this fact, the omentum of mice is considered an interesting organ for immune studies of peritoneal carcinomatosis, especially to understand the role of resident macrophages that promote peritoneal carcinomatosis [54][55][56]. However, on the whole, syngeneic PCa models are not entirely a bona fide model for PCa in patients.…”
Section: Pca Mouse Models 21 Pca Syngeneic Modelsmentioning
confidence: 99%
“…Despite this fact, the omentum of mice is considered an interesting organ for immune studies of peritoneal carcinomatosis, especially to understand the role of resident macrophages that promote peritoneal carcinomatosis [ 54 , 55 , 56 ]. However, on the whole, syngeneic PCa models are not entirely a bona fide model for PCa in patients.…”
Section: Pca Mouse Modelsmentioning
confidence: 99%
“…The combination of a CCR1 antagonist, CCX9588, with an anti-PDL1 antibody has proven to be a promising therapeutic approach, as it resulted in synergistic antitumoral effects by inhibiting primary tumor growth and lung metastasis in an orthotopic breast cancer mouse model [96]. Recently, in a mouse model of ovarian cancer, the small molecule inhibitor UCB35625 was also able to decrease cell migration towards the omentum, a preferential metastasis site in this type of cancer [97]. Overall, these results suggested that targeting CCR1 can be a viable therapeutic strategy to limit dissemination and potentially slow disease progression.…”
Section: Ccr1mentioning
confidence: 99%
“…Макрофаги БС способствуют миграции и колонизации клеток РЯ в нем путем продукции хемокиновых лигандов (CCL6 у мыши и CCL23 у человека), взаимодействующих с хемокиновыми рецепторами 1 (CCR1 -chemokine receptor 1), за счет чего активируются пути PI3K и ERK1/2. Истощение макрофагов уменьшает колонизацию БС раковыми клетками [18]. В экспериментах на мышах было показано, что за метастатическое распространение клеток РЯ отвечают в основном CD163 + Tim4 + резидентные сальниковые макрофаги [19].…”
Section: обзор литературыunclassified